2022
DOI: 10.1038/s41467-022-28632-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parameter photon-by-photon hidden Markov modeling

Abstract: Single molecule Förster resonance energy transfer (smFRET) is a unique biophysical approach for studying conformational dynamics in biomacromolecules. Photon-by-photon hidden Markov modeling (H2MM) is an analysis tool that can quantify FRET dynamics of single biomolecules, even if they occur on the sub-millisecond timescale. However, dye photophysical transitions intertwined with FRET dynamics may cause artifacts. Here, we introduce multi-parameter H2MM (mpH2MM), which assists in identifying FRET dynamics base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 85 publications
(93 reference statements)
0
37
0
Order By: Relevance
“…7 ). Recently, we studied YopO via multi-parameter photon-by-photon hidden Markov modelling, where the underlying apo distribution of YopO could be resolved 123 . We showed that apo YopO consists of two major FRET peaks that average on a sub 100 µs timescale to give one apparently “static” population.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Recently, we studied YopO via multi-parameter photon-by-photon hidden Markov modelling, where the underlying apo distribution of YopO could be resolved 123 . We showed that apo YopO consists of two major FRET peaks that average on a sub 100 µs timescale to give one apparently “static” population.…”
Section: Discussionmentioning
confidence: 99%
“…MpH 2 MM is an analytical method that extends classical hidden Markov modelling to the domain of single-molecule measurements. It has previously been used to identify within-burst dynamics originating from both conformational and photophysical dynamics in smFRET experiments 19 . As such, it excels at distinguishing between data containing a mixture of states, and data with a single state of more mixed nature.…”
Section: The Divisor Approachmentioning
confidence: 99%
“…We test from one to for divisors in the non-IRF scheme, and 1 to 4 divisors (which have n+1 divisors due to the additional divisor of the IRF) in the IRF scheme. All analyses were performed using the H2MM_C python package 19 .…”
Section: Mph 2 MM Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The HMM formalism is based on a discrete memoryless Markov process that infers a set of parameters (probabilities of states, transitions, and observations) to describe the observed sequence of FRET efficiencies. Many extensions of the HMM formalism have been developed 10 – 15 including Bayesian approaches 16 19 , and very fast kinetics (low energy barrier crossings) can be inferred from single-photon arrival times 20 22 .…”
Section: Introductionmentioning
confidence: 99%